Studi Keberadaan Industri Genteng Di Desa Kalirejo Kecamatan Kalirejo Kabupaten Lampung Tengah - Anita Khoiri Rohmah; Budiyono Budiyono; Rahma Kurnia Sri Utami (JPG (Jurnal Penelitian Geografi), 2017)
This research aimed to know about study of roof tiles industry existence in Kalirejo Village. This research uses dscriptive method. The data analysis was tabulation and percentage as the interpretation and description. The result showed that: 80,76% manufacturers were easy to obtain the materials, the necessity average all in were 1.283 m3/month materials. In the total of 80,76 % roof tile industry manufacturers were easy to obtain the labor, 18,24 % difficult. Most of the roof tile industry manufacturers were easy to gain the source of energy because of the agent who sold firewood. Every manufacturer claimed that they were easy in gaining the capital (89,18%), about 10,82% capital was private saving.100% the manufacturers were easy to fulfill the need of transportation. The total production of the roof tile industries were 1.239.583 roof tile/month 49.214 roof/manufacturers. About 84,62% manufacturers stated that the production process was smooth while the other 15,38% stated that it was not. Penelitian ini bertujuan untuk mengkaji studi keberadaan industri genteng di Desa Kalirejo. Penelitian ini menggunakan metode deskriptif. Analisis data menggunakan tabulasi dan persentase sebagai dasar interpretasi dan deskripsi. Hasil menunjukkan bahwa: 80,76% pengusaha mudah mendapatkan bahan mentah, rata-rata pengusaha membutuhkan bahan mentah sebanyak 1.283m3/bulan. 80,76% pengusaha industri genteng mudah mendapatkan tenaga kerja, 18,24% sulit. Seluruh pengusaha industri genteng mudah memperoleh sumber energi, karena ada agen penjual kayu bakar. Seluruh pengusaha menyatakan mudah mendapatkan modal, 89,18% berasal dari bank, 10,82% tabungan pribadi. 100% pengusaha mudah memenuhi kebutuhan transportasi. Total produksi genteng seluruh pengusaha 1.239.583 genteng/bulan atau 49.214 genteng/pengusaha. Sebanyak 84,62% pengusaha menyatakan lancar pemasarannya dan 15,38% menyatakan kurang lancar.Kata Kunci : Studi Keberadaan, Industri, Genteng